A STUDY OF ONLINE PURCHASE BEHAVIOUR- INVESTIGATING SOCIAL MEANING OF ONLINE PURCHASE IN TAIWAN - Chang, Che-wen (2008)
To justify the applicability of previous researches of online purchase in the Eastern culture, 237 samples in Taiwan are examined with questionnaire adapted from previous researches. Based on the assumption of rational behaviour that online purchase intention leads to behaviour, factors influencing them are examined and discussed. The result indicates that demographic attributes, perceived consequence, conspicuous meaning, information sources and reference group are confirmed to impact online purchase intention; while demographic attributes, impulsive consumption, information sources and reference group are proved to have influence on online purchase behaviour as previous Western-based researches concluded. However, the social meaning in East Asia is worth noticed in the conspicuous meaning and reference group. The conspicuousness desired in East Asia is based on the appreciation of group rather than self expression; while the appeal to be identified in a group i.e. online forum deriving consumer to purchase online. Both of them match the culture feature of collectivism in East country. Another discovery is the effectiveness of human opinion; which is more influential than online recommendation system while it presented in online format. The managerial implication to facilitate marketing tactics is given according to these finding.